Tantangan Manajemen Pendidikan Kristen di Era Modern - Sulifertia Saekoko; Lianti Kanna; Yanti Y.E Sole (Jurnal Ilmiah Literasi Indonesia, 2026)
This study examines the challenges faced by Christian education management in the modern era through a comprehensive literature review. The research identifies five main challenges: technology integration in learning processes, teaching quality and educator professionalism, adaptation to changing social values and norms, competition with general educational institutions, and limited financial resources. Using qualitative methodology with literature study approach, data were collected from books, journals, articles, and online sources to analyze challenges confronting Christian educational institutions. The findings reveal that these challenges are interconnected and require holistic management approaches. Christian education management can no longer rely solely on traditional approaches but must integrate innovation and modernization while maintaining fundamental Christian values. The study proposes strategic solutions including hybrid learning model development, professional learning communities for educators, funding diversification, and strategic alliances formation. Success in overcoming these challenges requires strong commitment from all stakeholders including institutional managers, educators, students, parents, and the broader Christian community. Christian education management must develop adaptive, innovative, and sustainable strategies to ensure the relevance and sustainability of Christian education in the future.